2012
DOI: 10.1007/s10840-012-9713-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of electrical cardioversion after cardiac resynchronization implantation in patients with permanent atrial fibrillation

Abstract: In patients with permanent AF, the rhythm control strategy consisting of internal cardioversion, performed by means of the implanted cardioverter-defibrillator after 3 months of CRT, was associated with a high rate of sinus rhythm resumption on long-term follow-up and with a better echocardiographic response to CRT than that seen in patients treated according to a rate control strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Two studies showed high cardioversion efficacy of ICD shocks in patients with paroxysmal or acutely induced AF [ 6 , 7 ]. Turco et al [ 4 ] evaluated cardioversion efficacy of ICD shocks in patients with a CRT-D device and permanent AF for more than 1 year. They found that 82 % of patients could be converted to stable sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies showed high cardioversion efficacy of ICD shocks in patients with paroxysmal or acutely induced AF [ 6 , 7 ]. Turco et al [ 4 ] evaluated cardioversion efficacy of ICD shocks in patients with a CRT-D device and permanent AF for more than 1 year. They found that 82 % of patients could be converted to stable sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with an implantable cardioverter-defibrillator (ICD), AF can be cardioverted with a synchronised internal shock from the ICD. Only limited data are available on the efficacy of internal ICD cardioversion for AF [ 4 ]. In the present study, we evaluated the effectiveness of internal cardioversion of AF in ICD patients.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually achieved through external cardioversion, but the presence of ICD gives an option to perform it through the implanted device as well. In fact, this approach was tested in small studies of patients with CRT-D 70 and ICD only, 71 where restoration of the sinus rhythm was achieved in 82% of cases, with only nonsignificantly better results of external cardioversion.…”
Section: Implantable Cardioverter-defibrillators In the Management Of Afmentioning
confidence: 99%
“…The only trial upon this issue was the non-randomized, cohort study of Turco et al . [ 17 ], which has shown a positive effect on end-diastolic volume in the rhythm control group, whereas the influence on ejection fraction was comparable between the rhythm and the rate control groups.…”
Section: Introductionmentioning
confidence: 99%